Sosialisasi Pendidikan Anti Korupsi Membangun Karakter Jujur Pada Anak Yang Kurang Aktif Dan Meningkatkan Minat Belajar Melalui Permainan Congklak Atau Dakon di SDN 004 Samarinda Ilir - Euis Kusumarini; Eka Selvi Handayani; Maria Yosevina Tridarmawati; Riska Wanti; Suwaibatul Aslamiyah (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to explain attempts to build honest character in less active children and increase their interest in learning through traditional congklak or dakon games. Congklak games were chosen because they have elements of competition that require honesty, while also involving fine motor activities that can stimulate the participation of children who tend to be passive. The method used is a literature methods based on literature review and analysis of earlier research result in PAUD, TK, and SD. The finding indicate that congklak these games prove beneficial in instilling honesty values, improving simple arithmetic skills, and triggering learning motivation in less active children. The strategies applied include the preparation of clear rules, providing positive encouragement, and reflection after the game. Thus, congklak games may serve as an alternative tool for educational purposes character and academics that are fun, both at school and at home, which are relevant to the developmental needs of early childhood to elementary school.